PENGARUH MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PUSKESMAS KUTA I KECAMATAN KUTA, BADUNG - Kusmara Dewi, Ni Wayan Grace; Made Suwandana, I Gusti (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.05.TAHUN.2024DO - 10.24843/EEB.2024.v13.i05.p13, 2024)
Employees with a high sense of job satisfaction and work motivation are able to provide good performance for the company. The purpose of this study is to determine the effect of work motivation and job satisfaction on employee performance. This research was conducted at Kuta I Health Center. The number of samples used was 136 employees of Kuta I Health Center, with a saturated sampling method. Data collection using questionnaires, data were analyzed using multiple linear regression analysis techniques. This study used the Two-Factor Theory. The results of this study show that work motivation has a positive and significant effect on the performance of Kuta I Health Center employees. Job Satisfaction has a positive and significant effect on the performance of Kuta I Health Center employees. Work motivation and job satisfaction simultaneously affect employee performance. The theoretical implications of the research support the Two-Factor Theory. Practically it can be a reference for other researchers who want or are interested in researching work motivation, job satisfaction and employee performance.